Partial Obstruction of the Small Intestine by a Trichobezoar in a Dog - Albernaz, Vinicius Gonzales Peres; Conceição, Renato Tavares; Eising, Talita Caterine; Fabris, Isabella de Almeida; Mamprim, Maria Jaqueline; Rahal, Sheila Canavese (Acta Scientiae Veterinariae, 2017)
Background: Bezoars are accumulations of foreign material and indigestible organic substances in the gastrointestinal tract. There are different classifications for bezoars based on its primary composition. The trichobezoars are concretions composed of hair or hair-like fibers and are often associated with trichophagia in humans. The obstruction by a trichobezoar occurring in the stomach, with its tail extending to or beyond the ileocecal valve or jejunum is rare in humans. This condition is called Rapunzel Syndrome. Obstruction by trichobezoar has been reported few times in cats and dogs. This paper aims to describe an uncommon clinical presentation of a young dog with partial obstruction of the small intestine by a trichobezoar. Case: A 2-year-old, 5.5 kg, intact male poodle was referred due to kyphosis and a history of pain in the thoracolumbar region for approximately 10 months. Physical examination revealed that the dog walked without any difficulty or ataxia, but had pain on palpation of the lumbar vertebral column. Thoracolumbar spine radiographies failed to show any sign of disease. Conservative therapy for intervertebral disk disease did not shown any improvement. In addition, the dog showed signs of pain on abdominal palpation and 18-month history of hyporexia, apathy and dark colored diarrhea. Abdominal ultrasonography detected a 5-cm intraluminal intestinal structure at the ileo-jejunal junction, forming an acoustic shadow, with focal thickening of the intestinal wall. Exploratory celiotomy followed by jejunal enterotomy revealed a trichobezoar consisting of undigested hair and textile fibers partially obstructing that segment. The intestinal wall in that region formed a sacculation, so a 5 cm jejunal resection with end-to-end anastomosis was performed. Histopathology of this segment did not show any neoplastic formation. After 20 days of surgical procedure, no clinical sign was reported by the owner, the animal return to normal appetite and back pain was not present. Ultrasonography confirmed normal intestinal flow. At the last follow-up 180 days after surgery, the dog was in excellent condition with no obvious clinical sign related to the disease or surgical procedure. Discussion: The mild chronic signs presented by the animal lead to an initial inaccurate diagnosis, since abdominal pain may seem like a back pain. The ultrasonography was useful to identify the presence of an initially unknow foreign body. However, definitive diagnosis was only possible after exploratory celiotomy, since trichophagia was not reported by the owner. The trichobezoar found in this case cannot be classified as Rapunzel Syndrome, since it is not a gastric trichobezoar with a tail extending up to the small intestine. The occurrence of trichobezoar is usually associated with overgrooming, tumor or end-to-end anastomosis, but none of this conditions was present. The presence of omental adhesion on jejunum wall is suggestive of previous damage, probably caused due to long-term permanence of the trichobezoar in this segment. The intestinal perforation caused by trichobezoar is one of the most common life-threatening complication observed in human patients. A sacculation observed during surgery may have contributed to its formation. The case presented may be considered extremely uncommon, due to the partial obstruction of the intestinal lumen and long-term evolution.